The Use of Social Media Technology in Educational Research at COVID-19 Time: Accounts and Problems - Muhammad Hanif; Herli Salim; Widjojoko; Tiurlina; Fatihaturosyidah (Jurnal Penelitian Pendidikan IPA, 2023)
The Covid-19 outbreak has impacted research since the government employs social distancing and physical distancing. As a matter of fact, the data collection process should use technology. This article aims to reveal the use of social media technology as a research tool during the pandemic time. This study focused on the potential and challenges of using social media in the educational research field. Basically, social media can be freely used by various circles, both in terms of cost and time spent. In addition, looking at the economic conditions during the declining Covid-19 pandemic, making social media can be used as an alternative tool compared to other technological platforms. Based on these facts, the authors are interested in studying social media as an alternative research tool in favor of the Covid-19 policy. This study revealed the high potential of social media use (Youtube, Instagram, and WhatsApp) in educational research. The low-cost feature of social media made this alternative should be considered although having some challenges. This study promoted social media as one of the alternative troubleshooting educational researches during the COVID-19 period. The research hopefully contributed to the development of technology for research at the limitation of the COVID-19 pandemic.